Non-isothermal kinetic applied to thermal decomposition of commercial alkyd varnish - Amaral, GCA; Crespi, Marisa Spirandeli [UNESP]; Ribeiro, Clovis Augusto [UNESP]; Hikosaka, M. Y.; Guinesi, L. S.; Santos, A. F. (Springer, 2005)
Samples of commercial alkyd resin varnish were spread in a film form on slides, dried at room temperature and exposed to solar radiation from one day up to seven months.Thermogravimetric measurements have been done. Based on the TG data, the Flynn-Wall isoconversional method was applied. The activation energy varied between 176-154 kJ mol(-1) and logA was between 15.5-12.9 min(-1) for A, B and C samples at 95% confidence level.
Keywords: alkyd resin; kinetic parameters; non-isothermal kinetic